Two new species of Dilaridae (Insecta: Neuroptera) with additional notes on Brazilian species - Machado, Renato José Pires; Rafael, José Albertino (Zootaxa, 2010)
Herein we describe two new species of lacewing in the family Dilaridae from northeastern Brazil: Nallachius furcatus, n. sp. and N. potiguar, n. sp. We also describe range expansions for three species: N. adamsi Penny, 1982 from Manaus to the border of the states of Amazonas and Pará; N. dicolor Adams, 1970 from the state of Santa Catarina to the states of Goiás and Minas Gerais; N. limai Adams, 1970 from Santa Catarina to Paraná. An identification key to adults and a checklist of Brazilian species are presented.